The Influence of miRNAs on Radiotherapy Treatment in Prostate Cancer – A Systematic Review - Soares, Sílvia; Guerreiro, Susana G.; Cruz-Martins, Natália; Faria, Isabel; Baylina, Pilar; Sales, Maria Goreti; Correa-Duarte, Miguel A.; Fernandes, Rúben (Frontiers in Oncology, 2021)
In the last years, extensive investigation on miRNomics have shown to have great advantages in cancer personalized medicine regarding diagnosis, treatment and even clinical outcomes. Prostate cancer (PCa) is the second most common male cancer and about 50% of all PCa patients received radiotherapy (RT), despite some of them develop radioresistance. Here, we aim to provide an overview on the mechanisms of miRNA biogenesis and to discuss the functional impact of miRNAs on PCa under radiation response. As main findings, 23 miRNAs were already identified as being involved in genetic regulation of PCa cell response to RT. The mechanisms of radioresistance are still poorly understood, despite it has been suggested that miRNAs play an important role in cell signaling pathways. Identification of miRNAs panel can be thus considered an upcoming and potentially useful strategy in PCa diagnosis, given that radioresistance biomarkers, in both prognosis and therapy still remains a challenge.